2003
DOI: 10.1083/jcb.200211046
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusins Mfn1 and Mfn2 coordinately regulate mitochondrial fusion and are essential for embryonic development

Abstract: Mitochondrial morphology is determined by a dynamic equilibrium between organelle fusion and fission, but the significance of these processes in vertebrates is unknown. The mitofusins, Mfn1 and Mfn2, have been shown to affect mitochondrial morphology when overexpressed. We find that mice deficient in either Mfn1 or Mfn2 die in midgestation. However, whereas Mfn2 mutant embryos have a specific and severe disruption of the placental trophoblast giant cell layer, Mfn1-deficient giant cells are normal. Embryonic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

96
2,055
4
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,198 publications
(2,231 citation statements)
references
References 51 publications
96
2,055
4
12
Order By: Relevance
“…We also performed the same experiment on explanted hippocampal neurons derived from 1‐ to 3‐day‐old mice and found a significant increase in ApoE4‐mediated PtdEtn synthesis (~1.8 ± 0.5), while the increase in PtdSer trended to significance (~1.7 ± 0.7) (Fig 1B). Notably, this increase in PtdEtn synthesis did not appear to be the result of increased expression of the PtdEtn biosynthetic machinery, as the expression of phosphatidylserine decarboxylase (PISD), a key enzyme of PtdEtn synthesis that converts PtdSer to PtdEtn within the mitochondrial matrix 30, was similar in ApoE3 and ApoE4 ACM‐treated fibroblasts (Fig EV2). …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We also performed the same experiment on explanted hippocampal neurons derived from 1‐ to 3‐day‐old mice and found a significant increase in ApoE4‐mediated PtdEtn synthesis (~1.8 ± 0.5), while the increase in PtdSer trended to significance (~1.7 ± 0.7) (Fig 1B). Notably, this increase in PtdEtn synthesis did not appear to be the result of increased expression of the PtdEtn biosynthetic machinery, as the expression of phosphatidylserine decarboxylase (PISD), a key enzyme of PtdEtn synthesis that converts PtdSer to PtdEtn within the mitochondrial matrix 30, was similar in ApoE3 and ApoE4 ACM‐treated fibroblasts (Fig EV2). …”
Section: Resultsmentioning
confidence: 93%
“…To establish that the increase in phospholipid production was indeed mediated by MAM, we performed the same assay using mouse embryonic fibroblasts (MEFs) in which the mitofusin 2 gene ( Mfn2 ) had been knocked out 30. Mfn2, in addition to its role in mitochondrial fusion, tethers ER to mitochondria 31; importantly, genetic ablation of Mfn2 reduces this connectivity 31.…”
Section: Resultsmentioning
confidence: 99%
“…Mfn1 is an essential protein for mitochondria fusion events. Accordingly, decreased Mfn1 function has been shown to trigger a profound shift in the fusion/fission balance, toward a dramatically fragmented mitochondrial network in most, if not all, cells and tissues tested to date (Chen et al , 2003; Park et al , 2008; Papanicolaou et al , 2012; Dietrich et al , 2013; Kulkarni et al , 2016). Further, While Mfn1 mRNA levels did not compensate for Mfn2 loss, we observed that Mfn1 protein slightly decreased in the BAT and WAT form Mfn2‐adKO mice (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, given that Mfn2 is a GTPase enzyme, we aimed to evaluate whether Mfn2 GTPase activity is required for the interaction. For this, we introduced wild‐type and GTPase dead (K109A; Chen et al , 2003) FLAG‐tagged forms of Mfn2 in differentiated brown adipocytes. The results (Fig 3G) illustrate that the introduction of GTPase dead Mfn2 mutants have an impaired ability to bind to PLIN1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SIRT1 overexpression reversed pathological events through its interaction with and subsequent deacetylation of MFN2. This mitochondrial outer membrane protein has diverse functions such as mitochondrial fusion (Chen et al., 2003), tethering between mitochondria and endoplasmic reticulum (ER) (de Brito & Scorrano, 2008; Naon et al., 2016), metabolic regulation (Bach et al., 2003; Sebastián et al., 2012), and the endocytic/secretory pathway (Daniele et al., 2014; Zhao et al., 2012). It is currently unknown how SIRT1 and MFN2 are affected by I/R in old hepatocytes.…”
Section: Introductionmentioning
confidence: 99%